Warriors warfare and the native American Indian - Bancroft-Hunt, Norman (Salamander Books Limited, 1995)
Fascinating, historically accurate, and exciting account of the great warriors and warrior tribes explores the beliefs, customs, and history of Native Americans from most regions of the U.S. Highlighted by the paintings of Kane. Vodmer, Catlin. Remington, Russell, et al. With archival b&w photographs. 250 illustrations, many in full color